PLTS Design for Small Industry Needs - Saut Situmorang (Journal of Science Technology (JoSTec), 2021)
The need for electricity both for industry, offices, as well as the general public and individuals is increasing. However, this increase in electricity demand is not accompanied by an increase in electricity supply. Based on these problems, solar energy was chosen as an alternative energy to produce electrical energy. The tool used here is a solar cell, because it can convert solar radiation directly into electrical energy (photovoltaic process). In order for solar energy to be used at night, during the day the electrical energy produced is stored in a battery controlled by the regulator. The regulator output is directly connected to the inverter from DC to AC current. The results of the solar module test (photovoltaic) show that the average output power reaches 38.24 Watt, and the current obtained is 2.49 A (Amperes). This is because the photovoltaic when following the direction of the sun's movement will always position the photovoltaic to remain facing the sun so that it will still be able to capture the sun's rays optimally.